Answer:
a. h(4) = -207
b. h(-2y) = 24y³ +12y +9
c. h(5b+3) = -375b³ -675b² -435b -90
Step-by-step explanation:
You want the simplified form of h(y) = -3y³ -6y +9 for using 3 different values of y.
The expression is evaluated by putting the argument where y is, then simplifying the resulting expression.
[tex]h(4)=-3(4)^3 -6(4) +9 = -3(64) -24 +9\\\\\boxed{h(4) = -207}[/tex]
[tex]h(-2y)=-3(-2y)^3-6(-2y)+9=-3(-8y^3+12y+9\\\\\boxed{h(-2y)=24y^3+12y+9}[/tex]
[tex]h(5b+3)=-3(5b+3)^3-6(5b+3)+9=-3(125b^3+225b^2+135b +27) -30b-18+9\\\\\boxed{h(5b+3)=-375b^3-675b^2-435b-90}[/tex]
__
Additional comment
It can be useful to remember that ...
(a +b)³ = a³ +3a²b +3ab² +b³